Confrontation by default and confrontation by design: strategic and institutional responses to Poland's populist coalition government. Issue 2 (23rd February 2016) - Stanley, Ben
Abstract : For a short and controversial period in 2006–2007, Poland was governed by a three-party "populist coalition" which attempted to break with the liberal-democratic model of post-communist transition and implement a far-reaching set of reforms. In this article, I analyse the ways in which domestic and external actors responded to the challenges posed by this coalition. I argue that Poland's Constitutional Court and the temporarily united opposition parties were key to repelling the populist challenge. However, the anti-populist response was driven less by a deliberate strategy than by the confrontational logic of populism itself, and the institutional design of Poland's liberal-democratic system. I conclude with a discussion of several lessons the Polish case holds for further analyses of anti-populist reaction.